PENGARUH WORK FROM HOME (WFH) TERHADAP TINGKAT EFEKTIVITAS KINERJA KARYAWAN PT. LANGGENG AGRONUSA PADA MASA PANDEMI COVID-19 - Widiastuti, Ina; Situmorang, Dokman Marulitua (Mount Hope Management International Journal, 2023)
The government appeals to the public to temporarily stay at home to prevent the corona virus (covid-19). This policy was intensified by creating a social distancing policy. Policies created such as work from home (WFH) aim to make it easier for employees to continue working during this pandemic. With this policy, some employees think that working from home is easy to implement. However, in its implementation several obstacles were found, for example there were no tools to do the work, reduced communication and coordination between employees, and so on. If it is not resolved immediately, a very complicated working system will arise. This scientific work seeks to find out how working from home affects the effectiveness of PT employee performance. Langgeng Agronusa so that you know what you have to pay attention to when working from home, so that it doesn't reduce work effectiveness.